Statutory minimum wages in the EU: Institutional settings and macroeconomic implications - Alfonso Arpaia; Pedro Cardoso; Aron Kiss; Kristine van Herck; Anneleen Vandeplas (Institute of Labor Economics (IZA), 2017)
This paper analyses some macroeconomic implications of the statutory minimum wage in the member states of the European Union and assesses how its institutional design influences these outcomes. First, the paper looks at the institutional dimensions of statutory minimum wage setting. On the basis of this information, an indicator of institutional stringency is built to characterise the degree of predictability of minimum wage setting. Second, it explores the impact of minimum wage changes on employment, prices, consumption, and poverty.
Keywords: J38; J52; E24; I32; 330; minimum wage; statutory minimum wage; composite indicator; poverty; in-work poverty; European Union